Structural and immunological analysis of circumsporozoite protein peptides: a further step in the identification of potential components of a minimal subunit-based, chemically synthesised antimalarial vaccine (2008)
The Plasmodium falciparum circumsporozoite protein is considered a major antimalarial-vaccine target due to its involvement in sporozoite invasion of mosquito’s salivary glands and human hepatocytes. The 4383, 4388 and 4389 CSP-conserved high activity hepatocyte binding peptides and their modified analogues were synthesised and their immunogenicity was tested in Aotus monkeys. Peptide 4388 modified analogues induced higher and more permanent antibody titers against sporozoites in ?40% of immunised monkeys; whilst peptides 4383 and 4389 modified analogues elicited high, long-lasting antibody titers as well as short-lived antibodies. 1H NMR studies showed that native peptides displayed random conformations, whereas most modified immunogenic HABPs contained type I, II and IV ?-turn structures. HLA-DR?1* molecule binding assays revealed that 4383 modified HABPs bound to HLA-DR?1*0701/HLA-DR?1*0401 molecules, whilst 4388 and 4389 modified HABPs bound to HLA-DR?1*0401/HLA-DR?1*0101, respectively. The results support these high-immunogenic CSP-derived modified peptides’ inclusion in a multi-antigenic, multistage, minimal subunit-based synthetic antimalarial vaccine.